Influence of metal mesh wettability on fog harvesting in industrial cooling towers. (25th November 2020) - Ghosh, Ritwick; Patra, Chandrima; Singh, Priya; Ganguly, Ranjan; Sahu, Rakesh P.; Zhitomirsky, Igor; Puri, Ishwar K.
Highlights: Maiden report on wettability-altered meshes for industrial fog water harvesting. Novel surface treatment to alter the wettability of stainless steel meshes. Scalable chemical etching and electrophoretic deposition methods adopted. Fog collection performance of wettability-altered meshes compared experimentally. TiO2 -coated hydrophilic metal mesh exhibits the best fog collection efficiency. Abstract: Fresh water stress can be alleviated by harvesting water from the fog plumes of industrial cooling towers (CT) using metal meshes. A typical CT fog harvester contains inclined meshes that intercept the rising fog plume. Water droplets deposit on these meshes and then roll down the surfaces due to gravity into a collection manifold below the mesh. The amount of water collected depends on the fraction of fog that is intercepted by the meshes and how the deposited water droplets drain off to the collector. Both fog interception by a mesh and water drainage from it depend on the wettability of the mesh and its inclination with the vertical. Through surface treatments involving either wet chemical etching of stainless steel meshes or electrophoretic deposition of TiO2 nanoparticles on them, we alter mesh wettabilities, making them super-hydrophilic (SHPL), hydrophilic (HPL), or super-hydrophobic (SHPB). Then, fog harvesting efficacy is investigated by placing these meshes in a vertical fog tunnel that resembles a scaled-down configuration of fog collector inside the CT-cell. The drainage from an untreated control mesh and an SHPB mesh are comparable, while SHPL meshes produce poor drainage for small inclinations. Overall, TiO2 -coated HPL meshes provide the best drainage which is maximum at a 15° mesh inclination angle.